(untitled) (Colombia Medica, 2011)
Introduction: The results of administering recombinant leptin, as well as the 116-130 peptide of mouse leptin in ob/ob mice have shown the probability of discovering more efficient leptin-based therapeutic methods to treat obesity. Objective: To demonstrate in Wistar rats fed with high-fat diet if the administration of synthetic peptides corresponding to the 116-130 peptide of mouse leptin (SR 116), its human homologue peptide (SH 95: sequence 95-109 from the 1AX8 protein) and five modified peptides (P80 to P84) similar to these two peptides, produces effects related to regulation of body fat. Materials and methods: Nine-week old Wistar rats were fed a high-fat diet for fifteen weeks. On the fifteenth week, and for five consecutive days, they were treated with the peptides to be evaluated. During the days of treatment, body weight and food intake were evaluated. After the last peptide administration, lipid profile, glycerol in the cellular medium, and DNA fragmentation in adipocytes were analyzed. Results: The results revealed that: the SR116 peptide affects the regulation of adiposity in rats fed a high-fat diet. The SH 95 is the human peptide with biological activity similar to SR 116 to lower weight, lessen food intake, and increase free glycerol in the cellular medium. The P80 and P81 peptides had a similar effect on SR 116 and SH 95 regarding body weight and food intake. The SR 116, SH 95 and three of the modified peptides (P80, P81, and P82) caused DNA fragmentation. Conclusion: The results suggest that peptides analogous to leptin are potentially viable to achieve effects of adiposity reduction in Wistar rats with obesity associated to high-fat diet; more research is rendered to explain the differences among peptides and the biological action mechanisms.